'Accessing something that's meant to be inaccessible': pornography viewers' reconciliation between early pornographic memories and pornography's perceived risk. Issue 1 (2nd January 2021) - Taylor, Kris
ABSTRACT: Is pornography more dangerous than ever before, or is there a gap between nostalgic memories of pornography and today's landscape of pornographic risk? In this study, the memories of pornography viewers are re-situated against a cultural backdrop in which pornography is understood as more dangerous than ever before. Using a combination of survey and interview data, the current empirical study works to understand how pornography viewers themselves reconcile their memories of early experiences with pornography within a contemporary environment that focuses on pornography's negative powers. The results suggest that adult pornography viewers do this through two primary mechanisms: by describing contemporary pornography as dangerous for 'other' people (but not themselves); and by accounting for their early experiences with pornography as positive, thereby perpetuating pornography's supposed effects as a problem for 'other' people. This article concludes with a discussion of how discourses of pornographic danger to young people engender a discursive environment in which young peoples' pornography viewing is simplified to a notion of risk, thereby foreclosing the sorts of considerations of pleasure and excitement allowed to adults.